Adsorption of As(III), As(V) and Cu(II) on zirconium oxide immobilized alginate beads in aqueous phase. (October 2016) - Kwon, Oh-Hun; Kim, Jong-Oh; Cho, Dong-Wan; Kumar, Rahul; Baek, Seung Han; Kurade, Mayur B.; Jeon, Byong-Hun
Abstract: A composite adsorbent to remove arsenite [As(III)], arsenate [As(V)], and copper [Cu(II)] from aqueous phase was synthesized by immobilizing zirconium oxide on alginate beads (ZOAB). The composition (wt%) of ZOAB (Zr-34.0; O-32.7; C-21.3; Ca-1.0) was confirmed by energy dispersive X-ray (EDX) analysis. Sorption studies were conducted on single and binary sorbate systems, and the effects of contact time, initial adsorbate concentration, and pH on the adsorption performance of ZOAB (pHPZC = 4.3) were monitored. The sorption process for As(III)/As(V) and Cu(II) reached an equilibrium state within 240 h and 24 h, respectively, with maximum sorption capacities of 32.3, 28.5, and 69.9 mg g −1, respectively. The addition of Cu(II) was favorable for As(V) sorption in contrast to As(III). In the presence of 48.6 mg L −1 Cu(II), the sorption capacity of As(V) increased from 1.5 to 3.8 mg g −1 after 240 h. The sorption data for As(III)/As(V) and Cu(II) conformed the Freundlich and Langmuir isotherm models, respectively. The adsorption of As(III), As(V), and Cu(II) followed pseudo second order kinetics. The effect of arsenic species on Cu(II) sorption was insignificant. The results of present study demonstrated that the synthesized sorbent could be useful for the simultaneous removal of both anionic and cationic contaminants from wastewaters. Graphical abstract: Highlights: Hydrous zirconium oxide-immobilized alginate beads (ZOAB) were synthesized. ZOAB successfully removed arsenite, arsenate and copper ion from aqueous phase. Addition of Cu 2+ was favorable for arsenate sorption. Maximum sorption capacities (qmax ) of ZOAB for AsO3 3−, AsO4 3− and Cu 2+ were 32.3, 28.5 and 69.9 mg g −1 . Sorption followed pseudo-second order kinetics.